Echocardiographic demonstration of free wall vegetative endocarditis complicated by a pulmonary embolism in a patient with ventricular septal defect. Issue 5 (May 1986) - Zijlstra, F; Fioretti, P; Roelandt, J R
Abstract : A defect in the muscular part of the interventricular septum in a 19 year old man was complicated by infective endocarditis caused by Staphylococcus aureus. The lesion was a large right ventricular free wall vegetation which embolised to the lungs. The vegetation was displayed by cross sectional echocardiography, which also confirmed the clinical diagnosis of ventricular septal defect. This case confirms the concept that the jet stream causes endocarditis at its point of impact. After six weeks' treatment with antibiotics the ventricular septal defect was repaired at operation.